Emotional arousal of beginning physics teachers during extended experimental investigations. Issue 2 (26th November 2012) - Ritchie, Stephen M.; Tobin, Kenneth; Sandhu, Maryam; Sandhu, Satwant; Henderson, Senka; Roth, Wolff‐Michael
Abstract Teachers often have difficulty implementing inquiry‐based activities, leading to the arousal of negative emotions. In this multicase study of beginning physics teachers in Australia, we were interested in the extent to which their expectations were realized and how their classroom experiences while implementing extended experimental investigations (EEIs) produced emotional states that mediated their teaching practices. Against rhetoric of fear expressed by their senior colleagues, three of the four teachers were surprised by the positive outcomes from their supervision of EEIs for the first time. Two of these teachers experienced high intensity positive emotions in response to their students' success. When student actions/outcomes did not meet their teachers' expectations, frustration, anger, and disappointment were experienced by the teachers, as predicted by a sociological theory of human emotions (Turner, J. H. (2007). Human emotions: A sociological theory. London, England: Routledge). Over the course of the EEI projects, the teachers' practices changed along with their emotional states and their students' achievements. We account for similarities and differences in the teachers' emotional experiences in terms of context, prior experience, and expectations. The findings from this study provide insights into effective supervision practices that can be used to inform new and experienced teachers alike. © 2012 Wiley Periodicals, Inc. J Res Sci Teach 50:137–161, 2013